PENENTUAN DENSITAS COLD DARKMATTER BERDASARKANDATAGUGUSGALAKSIDAN SUPERNOVAIA - Nahdhia Azhari, Ainun
Variousobservationshaveshownthattheuniverseisexpandingatanaccelerating rate. Onewaytoaccountfortheaccelerationistoaddacomponentwithnegative pressure, genericallytermeddarkenergy.Variousdarkenergymodelshavebeen proposed,thesimplestaswellasthemostsupportedbyobservationalfactsisthe cosmological constant().Ontheotherside,variousobservationalevidencefrom galactic toglobalscalesuggestthepresenceofdarkmatterasthedominantmatter in theuniverse.Inparticular,theformationoflargescalestructuressupportthe presence colddarkmatter,thenon-relativisticcomponentduringthegalaxyforma- tion era.Basedontheseobservationalfacts,CDMisgenerallyconsideredasthe standard modelofcosmology,inwhichtheuniverseisdominatedbycosmological constantandCDM( 0:67 and CDM0 0:28). Despitethesupportingobse- rvationalfacts,therearestillsomeproblemsremain.Darkenergyitselfisconfronted bycoincidenceandnetuningproblems.Asfordarkmatter,therearecore-cusp and missingsatellitesproblems,aswellastheparticlesareyettodetect.Alternative modelsareproposedtodealwiththeseproblems,althoughitisdiculttoovercome all ofthematonce.Forexample,amodelwithnon-gravitationalcouplingbetween dark matteranddarkenergyisproposedtodealwithcoincidenceproblem.This modelisalsosuggestedtodealwith H0 tension, thatisthediscrepancybetween the localHubbleconstantdeterminedusingdistanceladderandtheglobalvalue obtained fromcosmicmicrowavebackground(CMB)observation. In thisnalprojectthepresentvalueofcolddarkmatterparameterdensityisdeter- mined alongwithitsevolution.Furthermore,inordertotestanalternativemodel in whichcolddarkmatterinteractswithdarkenergy,thedeviationofdarkmatter evolutionfromthestandardevolutionofmatter( / a????3) isexamined. In thisFinalProject,galaxyclusters'gasfractionandluminositydistanceofSNeIa from PantheondatasetwereusedandMCMCmethodwasemployed.Theresultsof this FinalProjectshowedthatusingthecurrentgalaxyclustergasmassfractionand typeIasupernovadataanderrors,itisdiculttodierentiatetheinteractingCDM case fromthenon-interactingcase.Simulationusingmockdatashowedthatusing 1000 datapointsandhalftheerrorsofthecurrentgasmassfractionandluminosity distance datacouldnotdierentiatethetwocases.Adierentresultwasobtained byHolandaetal(2019)thatshowedthetwoscenarioswouldbedistinguishable using around500datapoints.